Ozone enhancement in western US wildfire plumes at the Mt. Bachelor Observatory: The role of NOx. (May 2015) - Baylon, P.; Jaffe, D.A.; Wigder, N.L.; Gao, H.; Hee, J.
Abstract: We looked at 19 wildfire events that were observed in the summers of 2012 and 2013 at the Mt. Bachelor Observatory (MBO, 2.7 km a.s.l.), a mountaintop site located in central Oregon. We identified wildfire plumes using enhancement ratios (Δ Y /Δ X ), which we calculated for each plume by taking the Reduced Major Axis linear regression slope of various species. We reported the calculated enhancement ratios and explored their relationship with ozone production. We observed a negative correlation between ΔO3 /ΔCO and ΔNO x /ΔNO y ( r  = −0.72). This showed that the degree of NO x oxidation is a key predictor of ozone production. The highest ΔNO x /ΔNO y (0.57 pptv/pptv) was associated with ozone loss (ozone titration). Low ΔNO x /ΔNO y values (ranging from 0.049 to 0.15 pptv/pptv) are generally associated with ozone enhancement. We also found that even if ΔO3 /ΔCO is low, ΔO3 may still be significant if CO enhancements are large. We then explored events that are not associated with any O3 enhancement/loss. Out of 19 fire events, 3 belong to this category. We discovered that these events are either BL-influenced (O3 deposition), associated with low ΔNO y /ΔCO ratios, and/or associated with minimal photochemistry (due to nighttime transport). Absolute ozone enhancements ranged from 3.8 to 32 ppbv, while ozone production efficiencies (OPEs) ranged from 2.1 to 17. However, because PAN comprises most of the reactive nitrogen in fire plumes, the calculated OPEs underestimated the true ozone mixing ratios. OPEs may therefore be misleading indicators of ozone production in wildfires. Finally, we segregated the data into plume/non-plume time periods. From this we found that the average O3 mixing ratio was significantly higher in fire plumes compared to non-plume time periods, and the noontime NO/NO2 ratios were also higher. This later result gives insight into the photochemical environment in the fire plumes. Highlights: We looked at 19 wildfire events at the Mt. Bachelor Observatory. We observed a negative correlation between ΔO3 /ΔCO and ΔNO x /ΔNO y . Even if ΔO3 /ΔCO is low, ΔO3 may still be high if CO enhancements are large. Ozone production efficiency ranged from 2.1 to 17. Boundary layer and nighttime transport can reduce O3 mixing ratios.